Sensors Technology in Sports Biomechanics: Exploring Applications and Advancements - Mojtaba Khadempir; Hassan Daneshmandi; Roya Bigtashkhani; Hosein Mohammad Alizadeh fard; Mohammadreza Saghafi (Biyumikānīk-i varzishī, 2023)
Objective Wearable sensors offer non-invasive, portable, and generally convenient ways to monitor sports training. This systematic review aims to present current evidence on using wearable sensors in sports for athletes. Methods IArticles published in English before May 2020 were searched in Scopus, Web of Science, PubMed, and EBSCO databases. Titles, abstracts, and keywords were probed with a search string including terms related to wearable sensors and sports. In addition to providing insight into how performance is achieved, these sensors also provide detailed kinematic, kinetic, and electromyographic information. Wearable sensors such as inertial sensors and electromyography are the most suitable from this point of view. Results Advances have been dramatic as sensors have become smaller, more precise, and capable of measuring more accurate data. Force plates measure the ground reaction forces that an athlete exerts while running, jumping, or landing. This information is critical in preventing injuries and understanding how different movement patterns affect performance. Strength platforms can also assess balance and stability, helping to develop injury prevention protocols and rehabilitation programs. Conclusion Reviewing the literature, inertial sensors are the most commonly used to evaluate athletes' performance. However, electromyography may also be used. Even though a wide range of sports was examined in the studies, running was the dominant sport evaluated. Therefore, researchers, athletes, and coaches find it helpful to understand current sports performance assessment technologies.